Body fat distribution and risk of incident ischemic stroke in men and women aged 50 to 74 years from the general population. The KORA Augsburg cohort study - Zahn, Karl; Linseisen, Jakob; Heier, Margit; Peters, Annette; Thorand, Barbara; Nairz, Franziska; Meisinger, Christa (PloS one, 2018)
It remains controversial whether measures of general or abdominal adiposity are better risk predictors for ischemic stroke. Furthermore, so far it is unclear whether body fat mass index (BFMI) and fat free mass index (FFMI) are risk predictors for ischemic stroke. This study examined the sex-specific relevance of body mass index (BMI), BROCA Index, waist circumference (WC), waist-height ratio (WHtR), BFMI and FFMI for the development of ischemic stroke in a Caucasian population. The prospective population-based cohort study was based on 1917 men and 1832 women (aged 50 to 74 years) who participated in the third (1994/95) or fourth (1999/2001) MONICA/KORA Augsburg survey. Subjects were free of stroke at baseline. Standardized anthropometric and bioelectric impedance measurements were obtained at baseline. Hazard ratios (HR) were estimated from Cox proportional hazard models. During a median follow-up of 9.3 years 128 ischemic strokes occurred in men and 81 in women, respectively. Coded as quartiles WC and WHtR were significantly associated with incident stroke in multivariable analyses in women (comparing the 4th vs. the bottom quartile), but none of the adiposity measures was significantly associated with incident stroke in multivariable adjusted analyses in men. When anthropometric measures were used as continuous variables, these findings were confirmed. After multivariable adjustment the associations between obesity measures and incident ischemic stroke were statistically significant only for WC (HR 1.39, 95%CI 1.12-1.72) and WHtR in women (HR 1.39, 95%CI 1.12-1.73) per increase of 1 standard deviation. In both sexes the measures BFMI and FFMI were no independent predictors for incident ischemic stroke. Abdominal obesity measures are independent predictors of incident ischemic stroke in women but not in men from the general adult population. Thus, it may be of particular importance for women to prevent central obesity in order to reduce their risk of ischemic stroke.